1993
DOI: 10.2307/1939306
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Western Spruce Budworm's Nutritional Niche With Response Surface Methodology

Abstract: A response surface design was used to help define the "nutritional niche" of the western spruce budworm, Choristoneura occidentalis. We evaluated how calcium, magnesium, and phosphorus interacted to influence budworm fitness on artificial diets containing five different levels of the minerals. We quantified survival rates for several life stages using a three—generation bioassay. Data from the bioassay were used to estimate population growth over three complete generations. Performance of the budworm was affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 25 publications
(20 reference statements)
8
50
2
Order By: Relevance
“…However, as shown here, it was observed that the lack of Mg in plants decreases the feed rate of the predators (CLANCY; KING, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…However, as shown here, it was observed that the lack of Mg in plants decreases the feed rate of the predators (CLANCY; KING, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…The caterpillar Manduca sexta exhibited faster growth and improved survival on artificial diets enriched in phosphate in the natural range, and also performed better on natural diets spiked with phosphate (Perkins et al, 2004). Similarly, higher leaf P levels were correlated with faster growth in spruce budworm caterpillars (Clancy and King, 1993), and the growth and survival of several lepidopteran larvae was better on wild and greenhouse-grown plants with higher %P, independent of %N (Apple et al, 2009). House crickets, Acheta domestica, grew and developed faster on artificial diets with a higher phosphate content (Visanuvimol and Bertram, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…However, observed effects of dietary phosphorus variation on insect herbivore growth in studies to date have not been consistent. Increasing dietary phosphorus has been shown to increase growth rates in caterpillars (Clancy and King, 1993) and crickets (McFarlane, 1991). Growth rates decreased in grasshoppers (Smith, 1960) and remained unchanged in mosquitoes (Dadd et al, 1973) in response to fluctuations in the amount of dietary phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Growth rates decreased in grasshoppers (Smith, 1960) and remained unchanged in mosquitoes (Dadd et al, 1973) in response to fluctuations in the amount of dietary phosphorus. The range of dietary phosphorus in three of these studies was not compared with the variation in phosphorus of the insects' natural diets (Smith, 1960;Dadd et al, 1973;McFarlane, 1991), and in the sole exception the minimum dietary phosphorus concentration was almost double the minimum observed foliar phosphorus concentration (Clancy and King, 1993). All but one of the studies were performed using only artificial diets.…”
Section: Introductionmentioning
confidence: 99%